2015
DOI: 10.1105/tpc.15.00898
|View full text |Cite
|
Sign up to set email alerts
|

The Structure-Specific Endonucleases MUS81 and SEND1 Are Essential for Telomere Stability in Arabidopsis

Abstract: Structure-specific endonucleases act to repair potentially toxic structures produced by recombination and DNA replication, ensuring proper segregation of the genetic material to daughter cells during mitosis and meiosis. Arabidopsis thaliana has two putative homologs of the resolvase (structure-specific endonuclease): GEN1/Yen1. Knockout of resolvase genes GEN1 and SEND1, individually or together, has no detectable effect on growth, fertility, or sensitivity to DNA damage. However, combined absence of the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…S2C). A very recent report showed that in Arabidopsis, SEND1 but not GEN1 acts as the functional Yen1/GEN1 homolog and plays an important role in toxic replication intermediate repair and telomere homeostasis in the absence of MUS81 (Olivier et al, 2016). In our study, we demonstrated that OsGEN1 but not OsSEND1 has indispensable roles in resolving meiotic and DNA replication intermediates in rice male reproductive cells.…”
Section: Osgen1 Is Irreplaceable For Male Reproduction In Ricesupporting
confidence: 60%
See 4 more Smart Citations
“…S2C). A very recent report showed that in Arabidopsis, SEND1 but not GEN1 acts as the functional Yen1/GEN1 homolog and plays an important role in toxic replication intermediate repair and telomere homeostasis in the absence of MUS81 (Olivier et al, 2016). In our study, we demonstrated that OsGEN1 but not OsSEND1 has indispensable roles in resolving meiotic and DNA replication intermediates in rice male reproductive cells.…”
Section: Osgen1 Is Irreplaceable For Male Reproduction In Ricesupporting
confidence: 60%
“…Two homologs of GEN1/Yen1 that are designated GEN1 and SEND1 exist across the plant kingdom (Olivier et al, 2016). It was reported that in Arabidopsis, AtSEND1 but not AtGEN1 acts as functional GEN1/Yen1 homolog.…”
Section: Ossend1 Is Not Essential For Rice Developmentmentioning
confidence: 99%
See 3 more Smart Citations